Extraction of Oil from Plants - Khalid M. Mousa Al-zobai; Mohammed Najem (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Black seed oil is a natural oil extracted from the seeds of Nigella sativa; a flowering plant was used as a case study of the recovery of oil from plants. This project is interested in the recovery of black seed oil using the Soxhlet apparatus with ethanol and cyclohexane as solvents. The extracted oil was weighed after one, three, and six extraction cycles for both solvents. Results indicated that the weight of the oil extracted increased significantly in the third and sixth cycles compared to the first. Subsequently, the black seeds were ground, and the extraction process was repeated using only ethanol as the solvent. This modification demonstrated an enhanced extraction efficiency. The findings suggest that the grinding of black seeds prior to Soxhlet extraction with ethanol as a solvent could be a more effective method for oil yield. The study provides valuable insights into the optimization of black seed oil extraction, which could be beneficial for industrial applications. The controlling step also studied and it was found that the mass transfer is the controlling step due to changes in the recovery when using different particle size and solvent.